DYNAMIC AND STATIC LIQUIDITY MEASURES IN WORKING CAPITAL STRATEGIES - Bolek, Monika (European Scientific Journal, ESJ, 2013)
﻿Liquidity management in a company may be analyzed in terms of the dynamic approach represented by the cash conversion cycle or the static approach represented by the current ratio. The mutual relationships between these measures change depending on the working capital level. The author considers the CR to be a dependent ratio, assuming that the CCC reflects the operational decisions affecting the level of current assets and liabilities. In the study, 61 regression models were used to assess liquidity ratios in non-financial companies listed on the Warsaw Stock Exchange in the period 1997–2010. In the aggressive and moderate strategies, the current ratio grew with the number of cash conversion cycles per year, while the relaxed policy resulted in the CR increasing with a decrease in the number of cash conversion cycles.